Perlukah E-Wallet Berbasis Syariah? - Nuha, Ulin; Qomar, Moh. Nurul; Maulana, Rafika Anissa (MALIA: Journal of Islamic Banking and Finance, 2020)
The purpose of this research is to find out about the transaction system in digital wallets (e-wallets) associated with the wadiah yad dhomanah contract in the study of muamalah fiqh. Whether the transaction is in accordance with the principles of Islamic finance so that it creates peace for Muslims in using the application.Digital payments are currently a public need along with the development of information technology in particular. This is evidenced by the non-cash payment innovation. This innovation in Indonesia was formally carried out by Bank Indonesia through the National Non-Cash Movement (GNNT) in 2014. This movement aims to increase public awareness of the use of non-cash instruments so that a community that uses cashless instruments is gradually formed (cashless). society).The technology cashless society clearly plays an important role in encouraging the consumption of Indonesia's middle class to be more consumptive. The presence of electronic money is one way to encourage people to become consumptive. The touch of technology in consumption through electronic money has provided a new color in interpreting consumption. Consumption does not only use its utility function to spend but also an identity function that needs to be fulfilled. Non-cash payment innovation in Indonesia continues to grow, along with the rise of financial technology (fintech) products in the form of digital wallets (e-wallets) such as Go-Pay, OVO, Dana, LinkAja, Paytren, and so on.